Direct steerable pipe thrusting - Robison, Jon (American Society of Civil Engineers, 2023)
"MOP 155 details how engineers and construction professionals can utilize the Direct Steerable Pipe Thrusting (DSPT) method to design and install pipelines"-- Provided by publisher.
Keywords: Underground pipelines -- Design and construction.; Pipe-laying machinery.; Trenchless construction.; Boring.; Directional drilling.; elektronické knihy; electronic books